2020
DOI: 10.21203/rs.3.rs-35332/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Andrà tutto bene”. The effect of character strengths on psychological distress and self-efficacy during Covid-19 lockdown

Abstract: The Covid-19 pandemic obliged people around the world to stay home and self-isolate, with a number of negative psychological consequences. This study focuses on the protective role of character strengths in sustaining mental health and self-efficacy during lockdown. Data were collected from 944 Italian respondents (mean age = 37.24 years, SD = 14.50) by means of an online survey investigating character strengths, psychological distress and Covid-19-related self-efficacy one month after lockdown began. Using pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Table 10 shows information about the papers analyzed for the study of compliance and social distancing. We chose to analyze anxiety because research on past epidemics, like SARS, MERS, swine flu and Ebola, revealed a wide range of negative psychosocial impacts, of which anxiety was one of the main outcomes [7,37,[183][184][185][186]. In particular, the quarantine had a huge impact on people: when comparing quarantined versus non-quarantined individuals, the first were more likely to show psychological distress and to have a high prevalence of psychological symptomatology [187].…”
Section: Results For Compliance and Social Distancingmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 10 shows information about the papers analyzed for the study of compliance and social distancing. We chose to analyze anxiety because research on past epidemics, like SARS, MERS, swine flu and Ebola, revealed a wide range of negative psychosocial impacts, of which anxiety was one of the main outcomes [7,37,[183][184][185][186]. In particular, the quarantine had a huge impact on people: when comparing quarantined versus non-quarantined individuals, the first were more likely to show psychological distress and to have a high prevalence of psychological symptomatology [187].…”
Section: Results For Compliance and Social Distancingmentioning
confidence: 99%
“…Higher levels of stress were associated with: loss of job/education [89,309], having to go out to work [187], having an acquaintance infected with COVID-19 [89,187,247], likelihood of contracting the virus [310], more hygiene behaviors [247,256,310], history of stressful situations [187], medical problems [74,187], risk perception and COVID-19 specific fear/worries [10,74,133,247,259,310], perception of changes in life [74], dysfunctional coping strategies (i.e., denial, substance use, behavioral disengagement) [55,74,245], loneliness [10], perceiving physical symptoms as COVID-19 [215], belief in conspiracy theories [46], low distress tolerance [10], low social support [10,55,276], and decreased sleep quality [271]. Protective factors for stress were associated with: resilience [259,311], greater social connectedness [276], seeking information on COVID-19 [74,89,183], up-to-date and accurate health information [186], functional coping styles (i.e., planning, religion) [74,245], internal locus of control [74], perception o...…”
Section: Results For Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the relationship between GSE and PR is complex, and the associated mechanisms are not yet clear. During the COVID-19 pandemic, research on GSE and PR usually addressed the psychological state of front-line medical staff and patients (Bidzan et al, 2020;Casali et al, 2020;Zhang J. et al, 2020). College students were mainly the target of descriptive research and analysis of the causes of changes in psychological status and behavior (Alemany-Arrebola et al, 2020;Ao et al, 2020;Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%